2019
DOI: 10.3390/ijerph16081354
|View full text |Cite
|
Sign up to set email alerts
|

Why Tenure Responsive Land-Use Planning Matters: Insights for Land Use Consolidation for Food Security in Rwanda

Abstract: Land use consolidation aims to address food insecurity challenges in Rwanda. However, there is contradictory evidence on whether this tool has met food security objectives or not. This study addresses two questions: How has the land use consolidation improved (or not improved) food security at the local level? How can food security challenges be addressed using a renewed approach to land use consolidation that adopts a tenure responsive land use planning procedure? We investigate these questions in Nyange Sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 43 publications
(120 reference statements)
0
17
0
Order By: Relevance
“…It is usually calculated through topographic maps or represented by the distance from land to road or market [46,47], and the impact of accessibility on land use is expressed by road accessibility and the impact degree of centre town. Human activities shape the natural landscape into a regular rectangular with distinct edges and corners, especially the agricultural land, and different sizes of plots form a checkerboard shape [27,48,49], a large number of studies have shown that agricultural land regulation can help improve land use efficiency [50][51][52].…”
Section: Construction Of Cultivated Land Evaluation Systemmentioning
confidence: 99%
“…It is usually calculated through topographic maps or represented by the distance from land to road or market [46,47], and the impact of accessibility on land use is expressed by road accessibility and the impact degree of centre town. Human activities shape the natural landscape into a regular rectangular with distinct edges and corners, especially the agricultural land, and different sizes of plots form a checkerboard shape [27,48,49], a large number of studies have shown that agricultural land regulation can help improve land use efficiency [50][51][52].…”
Section: Construction Of Cultivated Land Evaluation Systemmentioning
confidence: 99%
“…The land accounts will also improve access to credits, which will improve the productivity of smallholder farmers significantly [19,20]. The effects of land-use consolidation have been shown to differ based on the size of the consolidated land [21][22][23][24].…”
Section: Crop Intensification Program (Cip)mentioning
confidence: 99%
“…Land tenure and land titles would have featured prominently in early agricultural economies [14,15], but traditionally, land tenure security and agricultural productivity have been two separate areas of research. The link between land tenure security and agricultural productivity is therefore a relatively new subject [6,16]. Although recent decades have seen many publications research on the subject, the relation between land tenure and production continues to be conceptually described rather than operationally proven [17].…”
Section: Introductionmentioning
confidence: 99%